Accurate and efficient measurement of impurity (dilute) diffusion coefficients without isotope tracer experiments. (February 2017) - Zhang, Qiaofu; Chen, Zhangqi; Zhong, Wei; Zhao, Ji-Cheng
Abstract: Most impurity diffusion coefficients were measured in the 1960s and 1970s using tracer experiments with only 14 sets of tracer measurements performed worldwide in the past 15 years. It is thus impractical to rely on tracer experiments to obtain the missing thousands of impurity diffusion coefficients. A recently developed forward-simulation analysis can change the scenario by reliably extracting impurity diffusion coefficients from regular diffusion couple profiles. A comparison of 51 values obtained from the forward-simulation analysis with tracer experiment values in the literature shows an excellent agreement, thus validating the reliability of the forward-simulation analysis in obtaining accurate impurity diffusion coefficients. Graphical abstract: